Compression strapping for muscle injury on the ATP tennis circuit - Tintschl, M.; Bastholt, P.
This article describes the technique used for a combined elastic-rigid compression strapping of an injured muscle. Strapping of an injured muscle may allow the athlete to resume or continue sports activity with a mild strain. When the muscle injury is more severe (partial or complete muscle rupture), the loss of muscle potential and the risk of further damage can not be compensated for by strapping and prevents return to play until adequate tissue healing has occurred.